Konsep Teologi Perjanjian - Nino Sampe Tindih Sitohang; Helma Mesya C Siregar; Johanes GB Panjaitan; Kevin Boris A Marbun; Adi Suhenra Sigiro (Jurnal Silih Asuh : Teologi dan Misi, 2025)
Covenant Theology is a systematic approach to understanding the Bible that is based on the structure of the covenants God established with His people. It interprets the overall narrative of Scripture as a series of divine interactions built through three main covenants: Covenant of Salvation, Covenant of Works, and Covenant of Grace. Beginning with God's initiative to bind Himself to humanity, covenants form the basis for redemptive relationships and communicate His will in salvation history. This covenant history includes covenants with figures such as Adam, Noah, Abraham, and Moses, and their fulfillment in Jesus Christ, who is at the center of the New Testament. In the Reformed context, Covenant Theology explains the role of the Triune God in the work of salvation and forms the foundation for important doctrines such as salvation by grace, the sacraments, and the life of the believer. As such, Covenant Theology provides a holistic framework for understanding the biblical narrative as the consistent and loving unity of God to His chosen people.